Evaluating Frugivore-fruit Interactions Using Avian Eye Modelling - Nik Fadzly,; Kevin C. Burns,; Wan Fatma Zuharah, (Tropical Life Sciences Research, 2013)
Fruit phenotypes are often hypothesised to be affected by selection by frugivores. Here, we tested two hypotheses concerning frugivore-fruit interactions from the perspective of fruit colours. We measured the spectral properties of 26 fruits and the associated leaves of plants from 2 islands in New Zealand. Visual observations were also performed to record the birds that fed on the fruits. First, we tested the fruit-foliage hypothesis, where fruit colours are assumed to be evolutionarily constrained by their own leaf colour to maximise colour contrast and fruit conspicuousness. We ran a null model analysis comparing fruit colour contrast using an avian eye model. Second, we tested the frugivore specificity hypothesis, where specific fruit colours are thought to be connected with a specific bird frugivore. We performed a regression on the number of bird visits against the fruit colour in tetrahedral colour space based on an avian eye calculation using Mantel’s test. The results show that fruit colours are not constrained by their own leaf colours. There is also no relationship or pattern suggesting a link between a specific fruit colour and specific bird visitors. We suggest that although fruit colour is one of the most highly discussed components, it is not the most important single deciding factor in frugivore fruit selection. Fenotip buah biasanya dihipotesiskan dengan pemilihan oleh frugivor. Kami menguji dua hipotesis mengenai interaksi frugivor-buah dari perspektif warna buah. Kami mengambil bacaan spektra 26 buah dan daunnya dari 2 pulau di New Zealand. Pertama, kami menguji hipotesis buah-dedaun; warna buah dianggap bahawa terhalang secara evolusi oleh daun buah itu sendiri untuk memaksimakan kontra warna dan kejelasan buah. Kami menjalankan analisa model sifar perbandingan kontra warna buah berdasarkan model mata burung. Kedua, kami menguji hipotesis kekhususan frugivor; warna buah yang khusus dianggap berkaitan dengan burung frugivor yang khusus. Kami menjalankan regressi bilangan kunjungan burung dengan warna buah di dalam ruang warna tetrahedral berdasarkan pengiraan mata burung menggunakan ujian Mantel. Keputusan menunjukkan bahawa warna buah adalah tidak terhalang oleh warna daunnya sendiri. Tidak ada sebarang hubungan atau corak yang mencadangkan kaitan antara buah khusus dengan burung yang berkunjung khusus. Kami mencadangkan walaupun warna buah adalah satu komponen yang sering dibincangkan, warna buah bukan merupakan satu-satunya faktor penentu di dalam interaksi frugivor-buah.